Factors Affecting Distance Learning of the Physical Education Students of Sultan Kudarat State University, Mindanao, Philippines - Erlvira Lu Escomes; Chiarel Jean P. Gutierrez; Ian Paul C. Sarabia; Emy A. Morbo; Vivencio L. Calixtro Jr. (Universitas Pendidikan Indonesia (UPI), 2021)
This study investigates the factors affecting distance learning for Physical Education students. It used a descriptive method and a survey questionnaire using a google form to gather the data of the thirty-three second-year students. Results revealed that the said students have low motivation in doing their tasks such as assignments, reports, assessments, demonstrations, and oral recitation. In the perception of the students in terms of social presence and social interaction, they were dissatisfied when it comes to online discussions, conversing, interacting, participating, and speaking online. The students also preferred face to face mode of learning and this implies that future researchers should conduct and make a program that will help to make the students motivated in distance learning. The school administration especially the Bachelor of Physical Education department should implement more strategies and programs to increase the level of motivation, social presence, and social interaction of the students in today's distance learning due to the pandemic condition. The Commission on Higher Education should reduce and limit the number of students in each class as to approve the limited face to face class for the Physical Education students so that they may be able to do the task with proper execution and can be a big impact on the level of motivation, social presence and social interaction of the students, especially that these students preferred face to face mode of learning than online learning.